Negotiation, Adaptation and Women’s Resistance to Patriarchal Norms in the Context of Forced Marriage - Muhammad Fauzinudin Faiz; Ferhat Koca (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2024)
This study investigates the occurrence of coerced matrimony in a culture that prioritizes male-dominated principles, namely within the Muslim community. This study employs a qualitative methodology, which includes conducting in-depth interviews, organizing focus group discussions, and analyzing relevant documents. The findings of this study provide light on the several ways in which women who are confronted with forced marriage resist and adapt to their circumstances. The research findings indicate that a significant number of women face challenges when trying to obtain assistance and legal aid, which is worsened by societal disapproval and the insufficiency of current law enforcement measures. This study proposes enhancing awareness and education on women's rights, along with the necessity for legal restructuring to tackle the issue of coerced matrimony. These findings highlight the need for more extensive interventions and enhanced assistance for women who are confronted with forced marriage.